2018
DOI: 10.3390/app8071136
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Prestressed Concrete Beam for Straddle-Type Monorail Tracks

Abstract: Monorail transportation systems are widely built in medium and small cities, as well as hilly cities, because of their excellent performance. A prestressed concrete track beam is a key load-carrying structural component and guideway subjected to repeated traffic load. The fatigue behavior of the prestressed concrete beam is critical for the safety of the transportation system. This paper presents the results of an experimental study on the fatigue behavior of a prestressed concrete beam in terms of stiffness d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, differential cooling, creep, and shrinkage of bulb-tee cross sections are studied as potential reasons of crack growth. Kim and Gou et al [22][23][24][25][26][27][28][29][30] conducted experiments and comparisons between experimental results and design-equation predictions to determine the effects of steel-fiber and rebar reinforcements on the ultimate bearing strength of the local anchorage zone. The test and the comparisons between the design-equation predictions and the test results showed that the ultimate bearing strength and the section efficiency were highly affected by the reinforcement details and the concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the loading frequency of the fatigue test was between 2.4 Hz and 2.8 Hz. During the fatigue loading process, the repeated loading was first periodically paused, and the ballastless track was unloaded to zero when the fatigue cycle was ranged to 0 times (before the test), 500,000 times, 1,000,000 times, and every 500,000 times thereafter until 5,000,000 times [40]. Then the dial gauges were placed, ensuring that the pointers were in contact.…”
Section: Methodsmentioning
confidence: 99%
“…Pu, QH et al have studied the fatigue performance of PC beams in straddle monorail system, carried out stiffness degradation and strain change tests, tested the displacement and rotation of concrete beams and steel bars, and established a three-dimensional finite element model [14]. Gou et al have studied the dynamic characteristics of bridges under load by finite element method, and then, based on the simulation results, the influencing factors of bridges and evaluated the ride comfort of trains has been studied [15].…”
Section: Introductionmentioning
confidence: 99%